Blood-based biomarkers of cancer-related cognitive impairment in non-central nervous system cancer: A scoping review. (December 2022) - Oppegaard, Kate R.; Armstrong, Terri S.; Anguera, Joaquin A.; Kober, Kord M.; Kelly, Debra Lynch; Laister, Rob C.; Saligan, Leorey N.; Ayala, Ana Patricia; Kuruvilla, John; Alm, Mark W.; Byker, William H.; Miaskowski, Christine; et al.
Abstract: This scoping review was designed to synthesize the extant literature on associations between subjective and/or objective measures of cancer-related cognitive impairment (CRCI) and blood-based biomarkers in adults with non-central nervous system cancers. The literature search was done for studies published from the start of each database searched (i.e., MEDLINE, Embase, PsycINFO, Cumulative Index to Nursing and Allied Health Literature, Cochrane Central Register of Controlled Trials, grey literature) through to October 20, 2021. A total of 95 studies are included in this review. Of note, a wide variety of biomarkers were evaluated. Most studies evaluated patients with breast cancer. A variety of cognitive assessment measures were used. The most consistent significant findings were with various subjective and objective measures of CRCI and levels of interleukin-6 and tumor necrosis factor. Overall, biomarker research is in an exploratory phase. However, this review synthesizes findings and proposes directions for future research. Graphical Abstract: ga1 Highlights: Review focused on blood-based biomarkers of cancer-related cognitive impairment. Synthesizes the extant literature, including 95 studies. Highlights gaps in knowledge and areas for future research.